Sarcoidosis‐like reaction in metastatic triple negative breast cancer treated by anti‐PD‐L1. Issue 5 (4th June 2019) - Lafon, Mathilde; Blaye, Celine; Kind, Michele; Bechade, Dominique; Chassaigne, Florence; Italiano, Antoine; Grellety, Thomas
Abstract: We report the first case of sarcoidosis‐like reaction in a patient treated by anti‐PD‐L1 for a breast cancer. A 69‐year‐old woman presented with a histologically confirmed lung metastasis of a triple negative breast cancer. She was treated by nab‐paclitaxel plus anti‐PD‐L1 in first line. After 2 months, a dramatic lung response was noticed but an involvement of mediastinal lymph nodes appeared. Endoscopic ultrasound‐guided fine‐needle aspiration of these lymph nodes revealed multiple epitheloid granulomas without caseating necrosis in favour of a sarcoidosis‐like reaction. The patient remained free of symptom and in complete lung response on anti‐PD‐L1 treatment as a maintenance therapy.